Glauconite: a potential source for potash - Shirale, A. O.; Biswas, A. K.; Meena, B. P. (Indian Farming, 2018)
Considering the importance of potassium in crop production, future demand and cost on import of potassic fertilizer the use of glauconite directly as fertilizer can satisfy the fertilizer requirement of crops in future. Use of glauconite can also reduce the potassic fertilizer import by 50% in country. As it has very less weathering resistance power, so it can be used as slow release potassium fertilizer. Besides supplying potassium glauconite can also add appreciable amount of secondary (Mg) and micronutrient especially Fe Zn and Mo. Besides that application of glauconite improves the soil intrinsic properties like soil texture, waterholding capacity and cation exchange capacity etc. Hence, glauconite can be best option for potassic fertilizer in respect to improving crop productivity, soil health and also save the government revenue on import and subsidy on K fertilizers. The commercial mining of glauconite for preparation of concentrated glauconite fertilizer can create resources and generate employment for skilled-and-unskilled peoples.